Genetic manipulation of trehalose-6-phosphate synthase – a study on the functional activity and role in carbohydrate homeostasis in plants - Gabriel, Casey Ashley (Stellenbosch : Stellenbosch University, 2021)
Thesis (MScAgric)--Stellenbosch University, 2021.